Physico-Chemical Properties of Heattreated Layered Double Hydroxide Nanocomposites - Nadarajah, Sivajothi (1999)
Nanocomposite material of Zn/Al LDH-congo red (ZACORN), Co/ Al LDH-congo red (CACORN) and Zn/Al LDH-SDS (ZASDSN), were synthesised by spontaneous self-assembly of the inorganic and organic phase from homogenous aqueous solutions technique The X-ray diffraction patterns of heat-treated samples showed the formation of new phases ZnO and ZnA1204 at 900°C and 1000°C for ZACORN, C0304, C02AI04 and CoAh04 for CACORN and only ZnO for ZASDSN ZACORNs and CACORNs prepared at various concentrations of congo red showed that the concentration of congo red does not effect the basal spacing Quantitative analysis of colour difference, ∆E*ab, for TZACORNs and TCACORNs showed that they change exponentially with the heating temperature For TZASDSN, ∆E*ab increased rapidly at low temperature up to 300°C and then decreased as the temperature increased FTIR spectra showed the presence of four main peaks, 3700-3200 cm-1 is due to the hydroxyl groups, 1650-1500 cm-1 is due to the presence of water molecules, 1 130 cm-1 and 620 cm-1 is due to the presence of sulphate anion whereas peak at 800-400 cm-1 is Co-Al-O stretching and bending and metal-oxygen stretching. Scanning electron microscopy showed a mixture of amorphous and needle-like crystals for ZACORN, cubicle-like crystals for CACORN and spherical-like crystals for ZASDSN when heated at 900°C.